Inclusion of a care bundle for fever, hyperglycaemia and swallow management in a National Audit for acute stroke: evidence of upscale and spread - Purvis, Tara (Implement Sci, 2019)
BACKGROUND: In the Quality in Acute Stroke Care (QASC) trial undertaken in stroke units (SUs) located in New South Wales (NSW), Australia (2005–2010), facilitated implementation of a nurse-led care bundle to manage fever, hyperglycaemia and swallowing (FeSS protocols) reduced death and disability for patients with stroke. We aimed to determine subsequent adherence to the bundled FeSS processes (reflective of the protocols) between 2013 and 2017 in Australian hospitals, and examine whether changes in adherence to these processes varied based on previous participation in the QASC trial or subsequent statewide scale-up (QASCIP—Quality in Acute Stroke Care Implementation Project) and presence of an SU. METHODS: Cross-sectional, observational study using self-reported organisational survey and retrospective clinical audit data from the National Acute Services Stroke Audit (2013, 2015, 2017). Mixed-effects logistic regression was performed with dependent variables: (1) composite outcome measure reflecting compliance with the FeSS protocols and (2) individual FeSS processes, including the year of audit as an independent variable, adjusted for correlation of outcomes within hospital. Separate models including interaction terms between the year of audit and previous participation in QASC/QASCIP and year of audit and SU were also generated. RESULTS: Hospital participation included the following: 2013—124 hospitals, 3741 cases; 2015—112 hospitals, 4087 cases; and 2017—117 hospitals, 4192 cases. An 80% increase in the odds of receiving the composite outcome in 2017 compared to 2013 was found (2013, 30%; 2017, 41%; OR 1.8; 95% CI 1.6, 2.0; p < 0.001). The odds of FeSS adherence from 2013 to 2017 was greater for hospitals that had participated in QASC/QASCIP relative to those that had not (participated OR 2.1; 95% CI 1.7, 2.7; not participated OR 1.6; 95% CI 1.4, 1.8; p = 0.03). Similar uptake in adherence was evident in hospitals with and without an SU between 2013 and 2017. CONCLUSION: The use of the FeSS protocols within Australia increased from 2013 to 2017 with the inclusion of these care processes in the National Audit. Greater uptake in hospitals previously involved in QASC/QASCIP was evident. Our implementation methods may be useful for other national initiatives for improving access to evidence-based practice. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13012-019-0934-y) contains supplementary material, which is available to authorized users.